Design and Development of a Generative Artificial Intelligence-Based Application for Generating Online Article: Rancang Bangun Aplikasi Pembuatan Artikel Website Berbasis Kecerdasan Artifisial Generatif - Juan Manampiring; Alwin Sambul; Virginia Tulenan (Universitas Sam Ratulangi, 2025)
This study aims to design and develop a generative artificial intelligence-based article creation application for websites. By utilizing the ChatGPT API, this application enables users to automatically generate articles based on the provided input text. In this study, we identified the background of application development, formulated the problems to be solved, and established problem boundaries for research focus. The application development method was carried out through a web-based software design and development approach. The main objective of the research is to provide convenience and efficiency in article creation through the utilization of artificial intelligence technology. The results of this research are expected to contribute to the development of automatic content creation applications and enhance productivity in website article creation. The conclusion of this study is that the designed application is capable of providing an effective and efficient solution in the process of web-based article creation using generative artificial intelligence. Keywords - Artificial Intelligence; ChatGPT; Flask; Web; Website Articles.